Multiple Salivary Cortisol Measurements Are a Useful Tool to Optimize Metyrapone Treatment in Patients with Cushing’s Syndromes Treatment: Case Presentations - Yoshida, Kenichi; Fukuoka, Hidenori; Odake, Yukiko; Nakajima, Shinsuke; Tachibana, Mariko; Ito, Jun; Hosokawa, Yusei; Yamada, Tomoko; Miura, Hiroshi; Suematsu, Natsu; Matsumoto, Ryusaku; Bando, Hironori; et al. (Frontiers in Endocrinology, 2018)
Measuring salivary cortisol is both convenient and noninvasive for patients; however, its usefulness as marker for monitoring medical therapy has not yet been established. The aim of this study is to assess the utility of multiple salivary cortisol measurements in patients with Cushing’s syndrome (CS) during medical therapy. Six patients with CS (3 with cortisol-secreting adrenocortical adenoma, and 3 with ACTH-secreting pituitary adenoma) were recruited. Samples for morning serum cortisol, urinary free cortisol (UFC), and multiple salivary cortisol levels were collected before and during metyrapone treatment. The area under the curve (AUC) and mean value (MV) of daily salivary cortisol were calculated. Five out of 6 patients, UFC were normalized; however, multiple salivary cortisol measurement revealed an impaired diurnal cortisol rhythm in these patients. To verify the usefulness of multiple salivary cortisol measurements, we performed a prospective case study of a patient in whom the excess secretion of cortisol was not controlled (UFC 211µg/day) with 2250mg/day in 4 divided doses of metyrapone. Multiple measurements of salivary cortisol revealed that cortisol levels elevated before the next administration. Accordingly, we shortened the interval by increasing the number of administration from 4 to 5 times per day, with a slight increment of daily dose of 2500mg. These optimizations resulted in a drastic improvement of diurnal pattern as well as UFC level (101 µg/day). Changes in both the MV and AUC of salivary cortisol were more correlated to those in UFC (Correlation coefficient 0.75, p = 0.007, and 0.70, p = 0.017) than those in morning serum cortisol level (0.42, p = 0.200), indicating that multiple salivary cortisol measurement reflects more precisely the excess secretion of cortisol. Our preliminary data suggest that multiple salivary cortisol measurements can be a useful tool to visualize the diurnal cortisol rhythm and to determine the dose and timing of metyrapone during the treatment in patients with CS.